Lymphoplasmacytic Enteritis in a Young Cat - Souza de Moraes, Victória; Zanetti Patella, Lara; Moukaddem de Souza, Ísis; Dall'Agnol Krause, Catherine; Fett, Tobias; Fagundes da Costa, Henrique; Rodrigues Fett, Rochana; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2025)
Background: Chronic enteritis is a spectrum of gastrointestinal disorders that cause intestinal mucosal inflammation without a definite cause. The most common type of inflammatory infiltrate is lymphoplasmacytic enteritis (LPE), which mainly affects middle-aged felines, without gender or breed predisposition. The LPE is initially diagnosed through chronic gastrointestinal signs and exclusion of differentials. It is definitively diagnosed through histopathology and immunohistochemistry (IHC) based on a biopsy of intestinal segments. Therefore, this study primarily aimed to report a case of LPE in a young cat with less than 2 years of age having rarer occurrence than that observed in middle-aged animals. Case: A 1-year-and-8-month-old female cat, mixed breed, weighing 2.8 kg, with a body score of 5 (on a scale of 1-9), presented for treatment due to feces with a very strong odor, hematochezia, polydipsia, and polyuria. Tests for feline immunodeficiency virus and feline leukemia virus were negatives. The cat underwent 3 consecutive consultations, with blood, urine, and abdominal ultrasound tests. Despite showing improved biochemical and urinalysis results, they were still outside the reference values for the species. The image observed on ultrasound showed persistent changes related to the gastrointestinal system, such as thickening of the muscular layer of the wall in the small intestine segments, compatible with inflammatory infiltrate, and to the renal system, such as kidneys with reduced dimensions, irregular margins, marked loss of medullary-cortical definition, and dilation of both renal pelvises, indicating nephropathy and pyelectasis. She was treated for gastritis and underwent dietary treatment to screen for food-responsive enteropathy, which was nonresponsive. It was then opted for a biopsy via exploratory laparotomy, associated with elective ovariosalpingohysterectomy, to collect enteric samples. Histopathology and IHC tests were performed, which demonstrated invasion of lymphocytes, plasma cells, and eosinophils, confirming the diagnosis of LPE. Immunosuppressive treatment with prednisolone and dietary therapy was initiated, which effectively controlled enteropathy in this cat. Discussion: The diagnosis of LPE was based on clinical signs, imaging and laboratory examinations, histopathology, and IHC. The animal showed clinical signs compatible with chronic enteritis, such as diarrhea with hematochezia. During the exclusion of differential diagnoses, chronic kidney disease was evidenced in addition to chronic enteropathy. A biopsy of the intestinal loops was performed via exploratory laparotomy. Histopathology combined with IHC showed lymphoplasmacytic inflammatory infiltrate, the main characteristic of LPE, confirming the diagnosis of LPE. After the biopsy results, specific treatment with prednisolone was initiated, the drug of choice for immunosuppressive treatment in chronic enteritis or alimentary lymphoma. The clinical signs demonstrated by the cat that were necessary to initiate clinical reasoning, together with laboratory and imaging tests. A biopsy through exploratory laparotomy was essential, as it allowed samples to be collected so that IHC and histopathology could lead to a definitive diagnosis. Despite being a common pathology in elderly cats, lymphoplasmacytic enteropathy can be identified in younger cats. Therefore, LPE cases in patients less than 2 years of age should be reported, outside the age group considered most susceptible, so that veterinarians begin to consider this disease when faced with young animals showing clinical signs of chronic enteropathies. Keywords: feline, biopsy, chronic intestinal disease, histopathology, immunohistochemistry. Título: Enterite linfoplasmocitária em uma gata jovem Descritores: felino, biópsia, doença intestinal crônica, histopatologia, imuno-histoquímica.